Consumer Perception of Service Quality: Do We Need Industry Specific Scales or Can We Use SERVQUAL? An Analysis in The Context of The Airline Industry - Jochen Wirtz; Prem N. Shamdasani (Asian Academy of Management Journal, 1997)
Consumer Perception of Service Quality: Do We Need Industry Specific Scales or Can We Use SERVQUAL? An Analysis in The Context of The Airline Industry(PDF not available)